Pattern of Antibiotic Prescriptions in Chinese Children, A Cross-Sectional Survey From 17 Hospitals Located Across 10 Provinces of China - Zhang, Jiaosheng; Ma, Xiang; Tang, Lanfang; Tian, Daiyin; Lin, Li; Li, Yanqi; Lu, Gen; Si, Ligang; Zhang, Wenshuang; Qian, Jing; Wu, Lijuan; Liu, Gang; et al. (Frontiers in Pediatrics, 2022)
Objectives: Use of Broad-spectrum antibiotics is related closely to increasing antimicrobial resistance. The reports of antibiotic prescriptions for Chinese children were rare. We described the prescribing patterns of antibiotic prescriptions for Chinese children from 2017 to 2019 based on the Anatomical Therapeutic Chemical Classification (ATC classification); the Access, Watch, and Reserve (AWaRe) classification from the World Health Organization (WHO) and the Management of Antibiotic Classification in China. Methods: A 1-day point-prevalence survey (PPSs) on antibiotics prescribing for Chinese children was conducted in hospitalized children from 17 centers in 10 provinces in China from 1 September 2017 to 30 November 2019. Results: A total of 4982 antibiotic prescriptions for Chinese children were included in the analysis. There were 76 types of antibiotic agents in total, 22 (28.9%) of which accounted for 90% of all antibiotic prescriptions. The top-three antibiotics prescribed for children were azithromycin (684, 13.7%), ceftriaxone (508, 10.2%) and latamoxef (403, 8.1%). Third-generation cephalosporins (1913, 38.4%) were the most commonly prescribed antibiotic classes. On the basis of the AWaRe classification, the Watch group antibiotics accounted for 76.25% and Access group antibiotics accounted for 12.1% of all antibiotic prescriptions. On the basis of the China classification, we showed that 26.5% of antibiotic prescriptions were in the Unrestricted group, 53.6% in the Restricted group and 14.5% in the Special group. Conclusion: The proportion of antibiotics included in the Watch group and the special group was high in children in China. The AWaRe classification and China classification for antibiotic prescriptions could be used to supply detailed data for antibiotic stewardship as a simple metric.